Shark egg-case cross-link chemistry : biomimetic model of densely cross-linked collagen - Teh, John Wei Ming (2012)
Dogfish egg case is an elongated and leathery, oblong shaped vessel made up of collagenous-composite structure. Being an oviparous species, female dogfish sharks lay their eggs in the open water environment, protected only by its egg case.